Making connections across silos: intimate partner violence, mental health, and substance use - Robin Mason; Marni Wolf; Susan O’Rinn; Gabrielle Ene (BMC Women's Health, 2017)
Abstract Background Untold numbers of women worldwide are survivors of intimate partner violence (IPV) with a substantial number of these experiencing co-occurring mental health and substance use problems. Despite the complex interconnections among these problems, funding mechanisms and organizational structures and mandates have been designed to address just a single, focal problem. One of the challenges for frontline providers is the lack of effective, evidence-informed inter-professional education or training to help them identify and appropriately respond to co-occurring problems. We developed an evidence-informed, competency-based curriculum to address this gap. In this paper we report on its effectiveness in increasing knowledge, changing beliefs and enhancing skills of frontline workers from all three sectors. Methods The curriculum consists of multiple elements: a text manual; an interactive, online series of modules; and, an in-person workshop. Frontline workers (n = 1111) in the violence against women (VAW) (n = 499), mental health (n = 229), addiction treatment (n = 167), and associated sectors (n = 149) were recruited to attend the workshop and instructed to read the manual or complete the online modules before attending. Some failed to respond (n = 67). Online pre- and post-tests were used to assess changes in knowledge, beliefs and skills; evaluations of the workshop were also collected. Results Matched pre- and post-tests were available for over half of the participants (n = 624). Results show statistically significant improvements across all six competency domains from pre to post-test (p <0.0001). Significant changes in participants’ knowledge and stigmatizing beliefs were achieved. There was no correlation among differences in sector, age, size of organization, years of experience or prior training. Participant feedback made evident prior misconceptions about women experiencing co-occurring problems, improved understanding about the need to bridge silos, as well as the need for enhanced self-care. Conclusions An educational intervention designed to sensitize frontline workers to the realities of women’s experiences of co-occurring problems, educate about the challenges of accessing help when there are co-occurring problems, and bridge discipline and practice-based silos, can effectively challenge and alter providers’ negative attitudes and stigmatizing beliefs. Decreasing stigmatizing beliefs and increasing knowledge has the potential to help survivors access needed help.